Inter-rater and Intra-rater Reliability of the Chinese Version of the Action Research Arm Test in People With Stroke - Zhao, Jiang-Li; Chen, Pei-Ming; Zhang, Tao; Li, Hai; Lin, Qiang; Mao, Yu-Rong; Huang, Dong-Feng (Frontiers in Neurology, 2019)
Abstract Purpose: To detect the inter-rater and intra-rater reliability of the Chinese version Action Research Arm Test (C-ARAT) in participants with a first stroke. Methods: Fifty-five individuals (45 men and 10 women) with mean age of 58.67 ± 12.446 years (range: 22–80), and mean time after stroke of 6.47 ± 11.998 months (range: 0.5-80), were enrolled in this study. To determine the inter-rater reliability, the C-ARAT was performed by two varying levels of experienced raters (rater A and B) on each patient within 1 day. To determine intra-rater reliability study, 33 of the 55 patients were measured twice with C-ARAT by rater A with an interval of 1 day. The intra-class correlation coefficient (ICC) and Bland-Altman plots were used to analyze the inter-rater and intra-rater reliability. Results: For inter-rater reliability, the ICCs for the total, grasping, gripping, pinching and gross movement scores were 0.998, 0.997, 0.995, 0.997 and 0.960, all p ˂ 0.001, demonstrating the C-ARAT total and subscales scores had excellent inter-rater reliability in people with stroke. For intra-rater reliability, the ICCs for the total, grasping, gripping, pinching and gross movement scores were 0.987, 0.980, 0.975, 0.944 and 0.954, all p ˂ 0.001, demonstrating the C-ARAT total and subscales scores had excellent intra-rater reliability. The Bland-Altman plots showed a mean difference of 0.15 with 95% limits of agreement (95%LOA) from -2.16 to 2.46 in the inter-rater measurement and a mean difference of 1.06 with 95%LOA from -4.31 to 6.43 in the intra-rater measurement.. Conclusions: The C-ARAT showed excellent intra-rater and inter-rater reliability in evaluating the paretic upper extremity of individuals with stroke. Our results supported the C-ARAT to be used in stroke individuals.